Dimensões do trabalho pedagógico nos cursos superiores de tecnologia da UFSM: uma análise dialética - Fuentes, Rodrigo Cardozo (2017)
This thesis is part of the research line - School Practices and Public Policies - of the Postgraduate Program in Education (PPGE), from the Federal University of Santa Maria (UFSM). This study is based on the researches developed at Kairós Studies and Research Group and related to the theme "education and work" in a critical perspective, producing reflections about the Pedagogical Work (TP) at UFSM Higher Education Courses (CSTs). The present work is conduced and motivated by the belief that it has not been possible to overcome the contradiction between capital and work and perceiving that the clashes between social classes reflect in public policies in education and in the practices of educational institutions. It is a study constituted by a qualitative research, contextualized in the totality of the capitalist society and with theoretical-methodological reference based on dialectical historical materialism. The starting point is the belief that the training processes in the CSTs need a more adequate appropriation in the educational field and especially in the category of pedagogical work. These assumptions led to the following questioning: considering the Superior Courses of Technology in the context of the UFSM, to what extent, do the discourses on the pedagogical work of the teachers of these courses show the historical-ontological, pedagogical and socio-political dimensions? The Thesis developed two objectives: to propose a dialectical model in multidimensional perspective for the TP category and to perform the criticism to the TP of the CSTs of the UFSM, according to the developed perspective. When criticizing the TP in the CSTs of UFSM, it was possible to understand, among other aspects: the specificities of this modality of teaching; the articulation between theory and practice; the articulation between teaching, research and extension; the evaluation; the challenges of teachers facing this modality of teaching in a university institution; the relation of the TP with the collective of the students; and the processes of development of the theoretical objectives proposed and the actual implementation in the TP. Data production techniques, such as, the Survey and semi-structured interviews were applied, as well as documentary sources. The analysis of these data, produced in the empirical field, evidenced a set of mediations that allowed, along with the proposed multidimensional model, the criticism of TP in the CSTs of the UFSM, characterizing the dialectical movement of the phenomenon under study in search of its concreteness in the midst of Social totality. In addition to the criticism produced, paths for new studies are indicated from the multidimensional perspective presented for the TP category.